Relationship Between the Vascular Bundle Structure of Panicle Branches and the Filling of Inferior Spikelets in Large-Panicle Japonica Rice - You, Cuicui; Wang, Hui; Huang, Yaru; Xu, Peng; Wu, Liquan; Yu, Fuhan; Zhong, Xinyue; Gao, Jin; Zhang, Liangliang; He, Haibing; Ke, Jian (Frontiers in Plant Science, 2021)
The vascular bundles of rice panicles serve to connect the source and sink, as well as serving as a channel for the transportation of materials. In this study, two homozygous japonica rice strains were used as materials. The vascular bundle structures of the branches in different positions within a rice panicle were observed, and their cross-sectional areas were calculated. In addition, the ultrastructure of the central large vascular bundle (LVB) phloem in the rachillae of superior spikelets (SS) and inferior spikelets (IS) was observed during the grain filling period. Moreover, the soluble sugar and protein contents of the SS and IS rachillae was also measured to study whether the differences in the structure of vascular bundles of the branches were related to the plumpness of grain at different positions. The results showed that vascular bundle cross-sectional areas of the basal primary branches were greater than those in the upper primary branches. Moreover, there was little difference in the areas of vascular bundles between the basal secondary branches and upper secondary branches. However, the vascular bundle areas of the IS rachillae were lower than those in the SS rachillae. Therefore, we believe that the poor vascular tissue channel of the IS rachillae could be the limiting factor for IS plumpness. The results also showed that a similar time course in the degradation pattern of some organelles of the sieve elements and companion cells in central LVB was observed in the SS rachillae and IS rachillae during the grain filling period. Compared with the IS rachillae, more abundant mitochondria and plasmodesmata were found in the companion cells of SS rachillae at the beginning of filling stage, while no significant differences between SS and IS rachillae were identified at the middle and late filling stages, which implies that the SS rachillae were relatively more effective at transportation compared with the IS rachillae at initial filling stage. Therefore, the undeveloped vascular bundles of the IS rachillae and their poor physiology and lack of ability to transport at the initial filling stages could be the limiting factor for IS plumpness.